Foliar elemental composition of European forest tree species associated with evolutionary traits and present environmental and competitive conditions. Issue 2 (4th November 2014) - Sardans, Jordi; Janssens, Ivan A.; Alonso, Rocio; Veresoglou, Stavros D.; Rillig, Mathias C.; Sanders, Tanja GM; Carnicer, Jofre; Filella, Iolanda; Farré‐Armengol, Gerard; Peñuelas, Josep
Abstract Aim Plant elemental composition and stoichiometry are crucial for plant structure and function. We studied to what extent elemental stoichiometry in plants might be strongly related to environmental drivers and competition from coexisting species. Location Europe. Methods We analysed foliar N, P, K, Ca and Mg concentrations and their ratios among 50 species of European forest trees sampled in 5284 plots across Europe and their relationships with phylogeny, forest type, current climate and N deposition. Results Phylogeny is strongly related to overall foliar elemental composition in European tree species. Species identity explained 56.7% of the overall foliar elemental composition and stoichiometry. Forest type and current climatic conditions also partially explained the differences in foliar elemental composition among species. In the same genus co‐occurring species had overall higher differences in foliar elemental composition and stoichiometry than the non‐co‐occurring species. Main conclusions The different foliar elemental compositions among species are related to phylogenetic distances, but they are also related to current climatic conditions, forest types, drivers of global change such as atmospheric N deposition, and to differences among co‐occurring species as a probable consequence of niche specialization to reduce direct competition for the same resources. Different species have their own 'fixed' foliar elemental compositions but retain some degree of plasticity to the current climatic and competitive conditions. A wider set of elements beyond N and P better represent the biogeochemical niche and are highly sensitive to plant function. Foliar elemental composition can thus be useful for representing important aspects of plant species niches.